2021
DOI: 10.1002/pits.22510
|View full text |Cite
|
Sign up to set email alerts
|

What do French school staff know about young carers? A qualitative study about their perceptions

Abstract: Young carers (YCs) are children and adolescents who provide a significant help to family member(s) with a disease or a disability. They often remain hidden, especially in France where awareness levels and policy responses regarding YC are just emerging. Several studies show that YC often have difficulties at school because of their situation. However, school staff seems to have difficulties to identify and support YC. The aim of this study was to explore schools teachers and other professionals' levels of awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 40 publications
(65 reference statements)
4
17
0
Order By: Relevance
“…The aim was to explore these aspects among general school professionals and compare professionals according to their specific occupations within education. In line with the results of a qualitative study by Justin et al [ 13 ], we expected that social and healthcare professionals, as well as school counsellors would have more accurate perceptions than teachers, principals, and other professionals.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…The aim was to explore these aspects among general school professionals and compare professionals according to their specific occupations within education. In line with the results of a qualitative study by Justin et al [ 13 ], we expected that social and healthcare professionals, as well as school counsellors would have more accurate perceptions than teachers, principals, and other professionals.…”
Section: Introductionsupporting
confidence: 77%
“…However, it has been shown that YCs would like school professionals to be more aware of their family situations and to provide more support [ 2 , 7 , 12 ]. Therefore, school professionals may play a significant role in identifying and supporting YCs [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, boys can also be involved in care and should not be overlooked. This is all the more important because professionals know little about YCs (Justin et al., 2021; Leu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Such communication can help the teachers identify who is a young carer and to what extent, by better understanding their home situation and caring roles. This open communication between the parents and schools can also provide staff with more information and knowledge on young carers and how best to help them progress [ 62 ].…”
Section: Results and Interpretationmentioning
confidence: 99%